Automatic Classification of Turdus Rufiventris Song Notes By Spectrographic Image Template Matching - Souza Filho, Nilson Evilásio; Oliveira, Beatriz Cerimeli; Silva, Maria Luisa da; Vielliard, Jacques (Ciência e Natura, 2014)
This paper presents a method for automatic classification of birdsong notes. The elaborate method performs correlation calculationsapplied to spectrographic images to determine the similarity between the notes of a vocal repertoire, so the method was called SITM (Spectrographic Image Template Matching). The notes Nj of each phrase Pi which makes up the song of an individual of aspecie, are generally classified with letters of the alphabet according to the sequence emitted that is viewed in a spectrogram.By setting a minimum degree of similarity between the notes of the repertoire of each individual, it is possible to automate thistype of visual classification. Performance evaluation of automatic classification was performed with the vocal repertoire of threeindividuals of T. ruviventris recorded in to the wild. With 96% confidence, according to statistical inference, the rate of correctclassification via SITM was 77% to 97% of the notes in recording FNJV5915, 64% to 82% of the notes in recording FNJV5932and 74% to 97% of notes in recording FNJV5955.